Textisms and textese: A systematic review - Fernández Juliá, Olga; Gómez-Camacho, Alejandro (Revista Fuentes, 2023)
The aim of this article is to find out what scientific production exists on digital communication and the use of textisms between 2009 and 2022, which will allow us to identify which are the lines of research most worked on in this field, as well as to find the current state of the question. To this end, the systematic review methodology PRISMA (2021) has been used. After conducting the search and applying the exclusion criteria, a total of 62 articles were finally obtained from two databases: Web of Science and Scopus, after which the results were analysed. First, a quantitative analysis was carried out to find out how the published works were distributed in the selected years, in which journals they appeared the most frequently and to which countries and universities the authors with the most publications on the subject belonged. Second, a qualitative analysis has been carried out on the thematic lines they deal with and possible future lines of research. The results show a great disparity between the different articles, especially those dealing with the relationship between literacy and the use of textisms, which in turn show discrepancies in their conclusions on the relationship between the two variables.